1990
DOI: 10.1017/s0952523800003370
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive catecholaminergic ganglion cells in the pigeon retina

Abstract: An antiserum directed against tyrosine hydroxylase (TH), the rate-limiting enzyme in the synthesis of dopamine, was used to study the pigeon retina. Labeled cells were observed in both the inner nuclear layer (INL) and ganglion cell layer (GCL). Two populations of TH-immunoreactive neurons were observed in the INL. Some of these cells were 7-10 /im in diameter and gave rise to processes that arborized in three layers of the inner plexiform layer (IPL). These cells appeared similar to the dopaminergic amacrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 62 publications
1
9
1
Order By: Relevance
“…However, none of these regions contained double-labeled neurons, although cells containing the different markers were frequently found intermingled with one another in these zones. scribed by Keyser et al (1990). Although a small number of retinal ganglion cells are double-labeled following TeO injections and TH immunohistochemistry (Britto et al, 19891, and despite the occasional TH-immunoreactive fibers observed in layer 1, we could not detect any changes in the pattern of TH staining following either restricted scratch lesions or total retinal ablations.…”
contrasting
confidence: 49%
“…However, none of these regions contained double-labeled neurons, although cells containing the different markers were frequently found intermingled with one another in these zones. scribed by Keyser et al (1990). Although a small number of retinal ganglion cells are double-labeled following TeO injections and TH immunohistochemistry (Britto et al, 19891, and despite the occasional TH-immunoreactive fibers observed in layer 1, we could not detect any changes in the pattern of TH staining following either restricted scratch lesions or total retinal ablations.…”
contrasting
confidence: 49%
“…A more reliable way to distinguish GCs from ACs, however, is retrograde labeling of GCs. [35][36][37] In the retrogradely labeled mouse retina, the specificity of GABA, glycine, ChAT, and nNOS antibodies in labeling retinal ACs has been recently confirmed, 28 but similar investigations have not been done for TH, 38 CR, [32][33][34] and PV. [29][30][31] Of the multiple subtypes of ACs, GABA ACs are the only subtype that have been confirmed to couple with GCs.…”
mentioning
confidence: 99%
“…Keyser ct al. [20] report the presence of an additional population of presumptive THI ganglion cells in the gan glion cell layer (GCL). We demonstrate here that in quails, T H IR is observed in conven tional amacrine cells and IPCs both located in the amacrine cell sublayer of the INL.…”
Section: Resultsmentioning
confidence: 99%